The Vienna convention on diplomatic relations - Schiappa-Pietra, Oscar (2021)
The Vienna Convention on Diplomatic Relations adopted sixty years ago constitutes a unique example of international legislative success. The intensity of the processes of globalization and technological innovations, or the isolated cases of contempt by States, have not diminished its effectiveness as a fundamental instrument to promote international relations of peace and solidarity